The Internal Control of Public Administration and the Configuration of the Contemporary State - Rhein Schirato, Vitor (2019)
Nowadays, corruption scandals are rampantly and with increasing intensity exposing the misuse of public resources and the actions of dishonest public administrators. The use of scarce public resources has not allowed the hoped-for objectives to be reached. Even with no illegal act has been committed (here using the traditio-nal concept of illegality in Public Administration), it is not possible to ensure that public resources bring about the benefits expected by the population. With increasing frequency, the issue of control over public resources emerge. Consequently, local legislations and Admi-nistrative Law students look to create solutions to ensure Public Ad-ministration’s smoothness and the proper use of public resources, in order to create an environment that allows the collective purposes which justifies State collection of resources. However, the solutions in terms of control that come and are presented, cannot consider a sce-nario not present in Administrative Law, based on long-extinct struc-tures. If control is a tool destined to solve a problem, it seems funda-mental that this tool be in accordance with its field of application. It would be pointless to create a repair instrument that is useless for the damaged property’s characteristics. In this context, a discussion is formulated regarding the internal control of Public Administration. It follows that, in the control system of Administration itself and not by organs outside its organic structure, internal control is going through modifications and doctrinal discussions that aim to update it—althou-gh many times in disregard of the current Administration’s concept, structures and modus operandi. KEY WORDS: administration, internal control, public administration, effectiveness, purpose JEL CODE: H52, H72